Booktrailer y Booktuber como herramientas LIJ 2.0 para el desarrollo del hábito lector - Rovira-Collado, José (Investigaciones Sobre Lectura, 2017)
In the most recent formulas to promote reading, we focus on two dynamics that offer us many possibilities in schools to encourage reading habits of our students. Are Booktrailer, audiovisual books publicity like cinema and Booktuber, video reviews of the latest readings mainly young people shared across different Internet tools. New digital devices have favored recording, editing and publishing video, so the audiovisual and multimedia format becomes the perfect ally of reading. This paper want to do a description of both concepts, considering their advantages and disadvantages and especially the many possibilities of implementation in the educational field to work reading comprehension. For this show, various examples of good practices both dynamics to ensure that these digital products are an ideal support for the development of reading habits among students.